Effect of Poultry Manure and Ethephon on Growth, Yield, and Quality of Cayenne Pepper (Capsicum frutescens L.) ‘Ratuni UNPAD’ - Kusumiyati, Kusumiyati; Ramadhani, Rahmatillah; Maulana, Yusuf Eka; Hamdani, Jajang Sauman (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
The production of 'Ratuni UNPAD' cayenne pepper can be increased using organic chicken manure. However, the application of ethephon is needed during fertilization due to the significantly slow flower initiation. Therefore, this study aims to determine the interaction between chicken manure and ethephon on the growth, yield, and quality of the 'Ratuni UNPAD' cayenne pepper. Planting is carried out 829 meters above sea level (masl), and a factorial randomized block experimental design comprises 2 factors with 3 replications. The first factor is the dose of chicken manure (10, 20, 30, and 40 t/ha), while the second is the ethephon concentration (0, 500, 1000, and 1500 ppm). The results showed no interaction between poultry manure and ethephon on the growth, yield, and quality of the 'Ratuni UNPAD' cayenne pepper. According to the doses of chicken manure, 40 t/ha significantly affects the flower initiation, fruit number, weight, length, and diameter, as well as capsaicin and dihydrocapsaicin. The 30 t/ha shows the highest value for the number of leaves and productive branches, while 20 tons dose/ha influences flavonoids, phenolics, and total carotenoids. The ethephon concentration of 1500 ppm significantly affects the flower initiation, fruit length, diameter, capsaicin, and dihydrocapsaicin.